Traffic-driven low-power design and modeling of VLSI satellite switching fabrics - Wassal, A. G. (University of Waterloo, 2000)
The dream of the global village is rapidly becoming a fact of life with a dense and diverse web of communication links and technologies extending all over the world. However, a few spots here and there are yet to be connected. Moreover, the new nomads of the communication age demand to be connected whether in the sea, in the sky or on the road. Global satellite networks promised in the next few years, that move the backbone into the sky connecting people from virtually everywhere on earth, seem to be the answer. Nevertheless, these global satellite networks will not become a reality until a myriad of technical problems and issues are resolved. This work discusses the important issue of migrating the terrestrial packet switching fabrics on-board satellites. The approach is three-fold. First, the physical and performance constraints imposed by the new environment must be identified and used to choose and adopt a suitable fabric architecture from the wide variety available. Next, a mathematical model is formulated for the fabric architecture to optimize certain requirements, power dissipation in this case, under the remaining constraints. This is used to explore the design space at the system-level and choose appropriate values for different parameters such that the architecture satisfies the requirements and constraints. Finally, the buffer management problem and the scheduling engine design are investigated in more detail. The scheduling engine is one of the major components of the fabric and an architecture based on circular sorting queues is proposed, analyzed, and prototyped.
Keywords: Harvested from Collections Canada